O processamento da logoforicidade em português brasileiro - Souza, Flávia Gonçalves Calaça de (2020)
This paper seeks to examine the processing of logophoricity in Brazilian Portuguese (PB), more specifically the one expressed by the pro-forma himself in anaphoric and logophoric position. Authors such as Reinhart and Reuland (1993), Harris (2000), among others, point out that anaphors and logos are governed by different modules in Universal Grammar.According to these authors, anaphors are guided by syntactic factors such as location and c-command, while the logophore may or may not observe these syntactic conditions. Based on these theoretical assumptions, we performed three self-monitored reading experiments in order to find out if these differences are observed in the online processing of the subjects. Our hypothesis was that the processing of these two structures would be different and that the anaphors would be processed more quickly compared to the logos.The results found showed that the resolution of anaphors and logos is different, supporting the hypothesis formulated. In experiment 1, we obtained a significant result for the type of proforma (p <0.001) and we did not have a significant result for the concordance variable (p <0.63). In experiment 2 we found significant differences both for the type of proforma and for the agreement through ANOVA (p <.0.002) and (p <0.0004). Finally, in the third experiment, the result was significant for the type of proforma by ANOVA (p <.0,005) and had no significant result for the variable compliance. Thus, we obtained evidence that the syntactic factors guided the subjects when processing the anaphoric himself, however, for the logophoric himself other factors influenced the coreferential processing, going towards the theories explained in this thesis. Finally, we point out that the Theory of Reflexivity (Reinhart and Reuland, 1993) seems to be the most consistent to explain this phenomenon.